Loss of neurosteroid-mediated protection following stress during fetal life. Issue 160 (June 2016) - Hirst, Jonathan J.; Cumberland, Angela L.; Shaw, Julia C.; Bennett, Greer A.; Kelleher, Meredith A.; Walker, David W.; Palliser, Hannah K.
Highlights: Elevated neurosteroids during pregnancy have major protective and neurotrophic roles in the fetal brain. Preterm birth and maternal stress during pregnancy may deprive the fetus of adequate neurosteroid-mediated support. Neurosteroid therapy following preterm birth and compromised pregnancy may improve long-term outcomes. Abstract: Elevated levels of neurosteroids during late gestation protect the fetal brain from hypoxia/ischaemia and promote neurodevelopment. Suppression of allopregnanolone production during pregnancy leads to the onset of seizure-like activity and potentiates hypoxia-induced brain injury. Markers of myelination are reduced and astrocyte activation is increased. The placenta has a key role in maintaining allopregnanolone concentrations in the fetal circulation and brain during gestation and levels decline markedly after both normal and preterm birth. This leads to the preterm neonate developing in a neurosteroid deficient environment between delivery and term equivalence. The expression of 5α-reductases is also lower in the fetus prior to term. These deficiencies in neurosteroid exposure may contribute to the increase in incidence of the adverse patterns of behaviour seen in children that are born preterm. Repeated exposure to glucocorticoid stimulation suppresses 5α-reductase expression and allopregnanolone levels in the fetus and results in reduced myelination. Both fetal growth restriction and prenatal maternal stress lead to increased cortisol concentrations in the maternal and fetal circulation. Prenatal stress results in reduced expression of key GABAA receptor subunits that normally heighten neurosteroid sensitivity. These stressors also result in altered placental allopregnanolone metabolism pathways. These findings suggest that reduced neurosteroid production and action in the perinatal period may contribute to some of the adverse neurodevelopmental and behavioural outcomes that result from these pregnancy compromises. Studies examining perinatal steroid supplementation therapy with non-metabolisable neurosteroid analogues to improve these outcomes are warranted.